DISTINCTIVE FEATURES OF PERFORMING MUSICAL RHYTHMIC MOVEMENTS IN MUSIC LESSONS (Web of Teachers: Inderscience Research, 2025)
In this article, specific features of performing musical rhythmic movements in music lessons, educator E.The system of rhythmic upbringing, founded by Dalkroz, talks about the way in which the teacher chooses musical –rhythmic movements in accordance with the topic of the lesson and teaches it to students.